Transformation of the Ghent System in Sweden: Silent Institutionalization of Complementary Unemployment Benefits - Lindellee, Jayeon (Nordic Journal of Working Life Studies, 2021)
The Swedish public unemployment insurance program is characterized by its governance structure involving union-linked insurance funds, famously known as the Ghent system. This paper argues that the unions’ strongly entrenched interest in the provision of unemployment benefits has continued to shape the establishment and expansion of complementary benefits for the unemployed in multiple forms, including bilateral Employment Transition Agreements between employers’ organizations and unions (occupational pillar) and privately provided complementary income insurance benefits mediated by unions (private pillar). The paper accounts for this multi-pillarization process of the Swedish unemployment benefit provision system and how the unions’ involvement has come to take multiple forms. The paper also discusses distributive implication of this union-led development of the complementary pillars, which reinforces the differences in risk protection between different occupational groups and sectors.